Microstructural and Dielectric Properties of Ni-Zn and Li-Ni-Zn Ferrites by Impedance Spectroscopy. - Abdullah, Mustaffa; Yusoff, Ahmad Nazlim (Universiti Putra Malaysia Press, 1998)
The real and imaginary parts of the complex impedances and the loss angle (8) of iO.5Zn05Fe20, and (Lioleo.5)O.5Nio.2ZnO.3 Fe20, ferrites were measured at 300 K in the frequency range of 1 - 10 MHz using a frequency response analyser. The complex - plane impedance spectra of the samples are associated with equivalent circuits composed of resistive and capacitive elements due to the bulk (grain) and the grain boundary components. The measured and simulated impedances were analysed using the complex nonlinear least square (CNLS) fitting method. The simulated components of the circuit are interpreted as the characteristic parameters of the microstructural properties of the materials. Microstructural properties are complemented by a morphological study using a scanning electron microscope. The dielectric properties at low and high frequency regimes are interpreted as mainly due to the interfacial and orientational polarizations respectively. A region of negative capacitances at low frequencies is observed for both samples. Frequency dependence of the characteristic parameters of the microstructural components and the dielectric behaviour of the materials are discussed.